ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rosanna Purba (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2020)
The purpose of this study is to examine the influence of the factors that consist of firm size, Return on Assets (ROA), sales growth and leverage to tax avoidance on miscellaneous industry sector companies listed in Indonesia Stock Exchange. Each factors will be tested and analyzed partially and simultaneously on the tax avoidance. The population was manufacturing companies of 2015-2018 period that listed in the Indonesia Stock Exchange. The sample are obtained through purposive sampling which used miscellaneous industry sector companies listed in Indonesia Stock Exchange. The resources of data research are Indonesia Stock Exchange and company website. The method used in this study is a quantitative descriptive research approach. This research used multiple linear regression model by SPSS program. The result of this study is that partially Return On Assets (ROA) variable influences on the tax avoidance. Otherwise, firm size, sales growth and leverage variables have no influence on the tax avoidance. Based on the results of the simultaneous test, firm size, Return on Assets (ROA), sales growth and leverage variables together have influence on tax avoidance.